Low temperature activation of amorphous In-Ga-Zn-O semiconductors using microwave and e-beam radiation, and the associated thin film transistor properties - Seong Cheol Jang; Jozeph Park; Hyoung-Do Kim; Hyunmin Hong; Kwun-Bum Chung; Yong Joo Kim; Hyun-Suk Kim (AIP Advances, 2019)
In-Ga-Zn-O (IGZO) films deposited by sputtering process generally require thermal annealing above 300°C to achieve satisfactory semiconductor properties. In this work, microwave and e-beam radiation are adopted at room temperature as alternative activation methods. Thin film transistors (TFTs) based on IGZO semiconductors that have been subjected to microwave and e-beam processes exhibit electrical properties similar to those of thermally annealed devices. However spectroscopic ellipsometry analyses indicate that e-beam radiation may have caused structural damage in IGZO, thus compromising the device stability under bias stress.